Ways Ahead : Proceedings of the First International Csound Conference. - Heintz, Joachim (Cambridge Scholars Publishing, 2013)
The first international Csound conference, held at the Hanover University of Music, Drama and Media (HMTMH) between 30th September and 2nd October 2011, marked the first time that the principal people involved with Csound - in existence since 1986 - met in person. This book documents not only the proceedings of this conference through its inclusion of the featured papers, workshop descriptions and round table summaries, but also includes interviews with developers and musicians, along with se ...